The Effect of Health Belief Model-Based Training on Cervical Cancer Screening Behaviors - DEMİRGÖZ BAL, MELTEM (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: Cervical cancer remain a major public health problem, ranking as the fourth most common cause of cancer incidence and mortality in women worldwide in 2019. Prevention and early detection of cancer are considered as critical factors in controlling the disease and increasing the survival of patients. Therefore, we aimed to investigate the effect of Health Belief Model (HBM)-based education on cervical cancer screening behaviors. Methods: This is a descriptive type of study. The participants attended training workshops based on HBM. Data were collected by the questionnaire developed by the researchers and the Health Belief Model Scale Turkish version. Results: Twelve women (13%) from the participants had already taken the test before training. After training, the majority (n=56) of women had the Pap smear test (70%). Reasons for not getting a Pap-Smear Test (n=24) were determined as no need / no risk (n=13), no opportunity (n=7) and shyness (n=4) respectively. Conclusion: Our findings showed that the health education programs designed based on HBM could positively affect cervical cancer preventive behaviors.
Keywords: Health Belief Model; Pap smear; training program; cervical cancer; PAP-SMEAR TEST; WOMEN; PERCEPTIONS; KNOWLEDGE; ATTITUDES